Efficacy studies of phage phiIBB-Sep1 against S. epidermidis cells under different metabolic states - Melo, Luís D. R. (2012)
Staphylococcus epidermidis has recently become known as a usual cause of nosocomial infections, predominantly in patients with indwelling medical devices. Although, S. epidermidis infections only rarely develop into life-threatening diseases, they are very frequent and difficult to treat due to the ability of this bacterium to adhere to the surfaces of indwelling medical devices and form biofilms. When S. epidermidis cells are in a biofilm they are more resistant to antibiotics and to the immune system. The importance of biofilms in the pathogenesis of the S. epidermidis infections is becoming more understandable, consequently several studies are needed, in order to develop effective methods for biofilm control. The use of bacteriophages (phages) to eradicate biofilms can be seen as a potentially valuable approach. Phages are virus that infect bacteria and are the most abundant organisms on Earth. They are generally very efficient antibacterial agents and possess many advantages over antibiotics. Our aim is to search for virulent phages with broad host range for S. epidermidis biofilm therapy. Using wastewater treatment plants raw effluents we were able to isolate 5 phages. Their lytic activity was screened against 40 clinical S. epidermidis isolates with different genetic profiles and it was found to be different ranging from 46% to 95% of positive results. Further morphologic and genetic characterization of these isolated phages is now being performed. Efficacy studies results show that phage phiIBB-Sep1 is able to cause a 6 Log CFU/ml reduction of the cell titre in <2h for some of the clinical strains at exponential phase and in <4h for stationary phase cells (using a MOI of 1). This phage has also the capacity of reducing by up to 2 Log CFU/ml 24h biofilm cells and in some strains it was observed 50% cell reduction on biofilms. Besides CFU counting, all the cell counts were confirmed by flow cytometry assays. Additionally, flow cytometry allow the observation that this phage kill cells under different metabolic states from the biofilm. Work developed with non biofilm forming strains showed that possibly PNAG might be the cell receptor of the phage. The high amounts of PNAG on biofilms, might the lower activity of this phage on biofilms. These are promising results, since phage phiIBB-Se1 presents a broad host range and ability to control S. epidermidis under different metabolic states. Ongoing studies are being performed with 4 other phages, with the purpose of developing a phage cocktail to be used against S. epidermidis biofilm infections.